Collaborative Governance Sebagai Upaya Pengembangan Ekosistem Ekonomi Kreatif di Kabupaten Bojonegoro : Penelitian - Fruri Stevani; Niken Widoretno; Ferri Irawan (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The creative economy is a strategic sector in national economic growth, where the role of the government and the private sector is crucial in creating a conducive ecosystem. Collaborative governance with various parties is a concrete effort to achieve the shared goal of realizing Bojonegoro as a creative city supported by the formation of a creative economy ecosystem in Bojonegoro Regency. This study uses qualitative research methods. Data in this study were obtained from primary and secondary data, while data collection techniques were carried out through observation, interviews, and documentation. This study shows that collaborative governance in the creative economy program in Bojonegoro Regency has been realized quite well. The government plays a role in providing adaptive and facilitative policies, while other collaborative sectors contribute to investment, technology, and broader business networks. Some key challenges include complex bureaucracy, lack of cross-sector coordination, and disparities in access to resources. To optimize this partnership strategy, a collaborative approach based on shared interests, transparency, and increased human resource capacity is needed.